A Novel Ultrawideband Transmitarray Design Using Tightly Coupled Dipole Elements - Cai, Yuan-Ming; Li, Wenting; Li, Ke; Gao, Steven; Yin, Yingzeng; Zhao, Luyu; Hu, Wei (IEEE transactions on antennas and propagation, 2019)
One of the key challenges in transmitarray (TA) designs is its narrow bandwidth. To overcome this limitation, this paper proposes a novel design of ultrawideband TA antenna based on tightly coupled dipole arrays (TCDAs). The array consists of 20 × 10 unit cells, and each unit cell is composed of a pair of short dipoles connected with a section of meandered transmission line. The size of each unit cell is 20 \text {mm} × 10 mm, which is about 0.2λ × 0.1λ , where λ is the wavelength in free space at the lowest working frequency of the TA. By utilizing the strong coupling between adjacent units of the TA, the bandwidth of the TA is improved significantly. To verify the design concept, one prototype of the proposed TA is fabricated and measured. The prototype demonstrates good performance over a bandwidth of 104%, i.e., from 3.0 to 9.5 GHz, which is significantly wider than that of other TAs reported in the literature. Within the working band of the TA antenna, the radiation pattern is stable and no distortion or splitting of the main beam of the antenna is observed. This is the first time that the TA based on TCDA is reported.